Instrumental characterization of xanthan gum and scleroglucan solutions: Comparison of rotational rheometry, capillary breakup extensional rheometry and soft-contact tribology. (September 2022) - Li, Xinxin; Harding, Stephen E.; Wolf, Bettina; Yakubov, Gleb E.
Abstract: Xanthan gum and scleroglucan, two rod-like polysaccharide hydrocolloids, are compared using a wide range of instrumental techniques and methods: steady shear flow, small amplitude oscillatory shear, first normal stress difference, capillary break-up and soft-contact tribology. The aqueous solutions of these two hydrocolloids with similar flow and viscoelastic profile show marked differences in capillary break-up time and apparent extensional viscosity. This result correlates with differences in first normal stress difference and, to a lesser extent, Stribeck curve behaviour. Formulating the hydrocolloids in concentrated sucrose solution (40 wt%) shifts relaxation profiles to longer times which greatly diminishes differences in rheological and lubrication behaviour. With exception of capillary break-up tests, no other methods showed statistically significant differences between the polysaccharides dissolved in the viscosified matrix. The toolbox of techniques is also applied to probe interactions of xanthan gum and scleroglucan with human whole saliva and bovine submaxillary mucin. We report no specific interactions between either hydrocolloid and salivary proteins and suggest that any cumulative effects must stem from specific sets of linear and non-linear rheological properties of saliva/hydrocolloid mixtures. Graphical abstract: Image 1 Highlights: Rheology and tribology of xanthan gum and scleroglucan are compared. Capillary break-up provides sensitive discrimination between hydrocolloids. Xanthan gum and scleroglucan have similar hydrodynamic volume. Relaxation spectrum of xanthan features faster modes compared to scleroglucan.